2004
DOI: 10.1021/ol036143i
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Reduction of Cyclopropenylcarbinol:  New Access to anti-Cyclopropylcarbinol Derivatives

Abstract: [reaction: see text] Cyclopropenylcarbinol derivatives are regio- and diastereoselectively reduced with LiAlH(4) in Et(2)O into trans-cyclopropylcarbinols as a single isomer. The regioselectivity of the hydroalumination reaction on the cyclopropenyl ring has been mapped out by deuterium labeling experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…[37] This result indicated an S configuration for the hydroxyl-substituted stereocentre in alcohol 15. Additionally, hydroalumination of the minor cyclopropenylcarbinol 14 [38] and subsequent treatment of the resulting compound 17 with DDQ (anhydrous conditions) provided para-methoxybenzylidene acetal 18 (52 %, 83:17 epimeric mixture at the acetal stereocentre), the relative configuration of which was confirmed by 1 H NMR spectroscopy (Scheme 10). Application of the Felkin-Anh model [39] would have predicted cyclopropenylcarbinol 14 to be the major diastereomer, which is not experimentally observed.…”
Section: Resultsmentioning
confidence: 94%
“…[37] This result indicated an S configuration for the hydroxyl-substituted stereocentre in alcohol 15. Additionally, hydroalumination of the minor cyclopropenylcarbinol 14 [38] and subsequent treatment of the resulting compound 17 with DDQ (anhydrous conditions) provided para-methoxybenzylidene acetal 18 (52 %, 83:17 epimeric mixture at the acetal stereocentre), the relative configuration of which was confirmed by 1 H NMR spectroscopy (Scheme 10). Application of the Felkin-Anh model [39] would have predicted cyclopropenylcarbinol 14 to be the major diastereomer, which is not experimentally observed.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, Zohar and Marek have shown that the diastereoselectivity of the LiAlH 4 reduction of cyclopropenes can be controlled when the substrate is a secondary allylic alcohol [90]. The diastereoselectivity is particularly high when the substrates are derivatives of 3,3dimethylcyclopropene.…”
Section: Facially Selective Hydrometallation Of Cyclopropenesmentioning
confidence: 99%
“…[7] Ideally, if one could prepare these quaternary stereocenters in a single-pot operation from simple starting materials through a selective carbon-carbon bond activation, it would not only answer this challenging synthetic problem but also pave the way for the efficient formation of new functionalized adducts.Our plan was to initially perform a diastereoselective carbometalation reaction of the cyclopropenyl ester 1 to give the diastereomerically enriched functionalized cyclopropylmetal species 2 (Scheme 1). [8] Then, in a subsequent step, 2 would be oxidized into the corresponding metal cyclopropanolate 3 which would undergo a regioselective ring-opening reaction to provide the versatile metal homoenolate 4. [9] Aldehydes 5, bearing the expected all-carbon quaternary stereocenters in acyclic system, would then be obtained after acid hydrolysis, The entire sequence would proceed in a single pot from the starting alkene.…”
mentioning
confidence: 99%
“…[11] Importantly, the metal-catalyzed enantioselective cyclopropenation of terminal alkynes with diazoacetate and Rh II , Co II , or Ir II catalysts are well established methods and as a result, 2-substituted 2-cyclopropenecarboxylic acid esters (1) are easily obtained with excellent enantiomeric ratios and yields. [8,12] So, from the enantiomerically enriched 1, easily prepared from simple terminal alkynes, the formation of these challenging aldehydes (5) could be carried out in a single-pot operation through a sequence of diastereoselective carbometalation/oxidation/ selective ring-opening reactions (Scheme 1).The diastereoselectivity of the carbometalation should be controlled by the stereogenicity of the carbon atom holding the ester moiety (C1; Scheme 1). In the subsequent reactions, this point of chirality is transferred upon selective C3ÀC1 bond activation to give the enolate 4 with an all-carbon stereogenic center.…”
mentioning
confidence: 99%
See 1 more Smart Citation